The Correlation of Retinol Level with Hemoglobin Level in Third Trimester of Pregnancy Woman - Febry Mutiariami Dahlan; Eryati Darwin; Hirowati Ali (Universitas Andalas, 2018)
Bleeding is one of the highest causes of maternal death. Anemia is a major cause of bleeding. Anemia in pregnant women is caused by iron deficiency, meanwhile the achievement of giving Fe tablets is quite high. Factors for anemia due to lack of intake of vitamins A, C, B12 and folate.This study aims to determine the Correlation Retinol Level with Hemoglobin Level and Ferritin Level in Pregnant Women Thiird trimester. This study was conducted using cross sectional approach, from Juli 2017 – February 2018 at Lubuk Buaya Health Center, Andalas Health Center and UNAND Biomedical Laboratory using pregnant women in third trimesteras sample with consecutive sampling technique totalling 44 people. Independent variable is retinol level and dependent variable are hemoglobin and ferritin level. Examination using Hematology Analyzer for hemoglobin and ELISA reader for examination of retinol level and ferritin level. Data was performed using a computer program to analyze nprmally distributed data using pearson test and spearman test that are abnormally distributed. Mean of retinol level of respondent was 137,612±21,717 ng/ml, hemoglobin 10,916±0,880 gr/dl and ferritin level 26,681±30,829 ng/ml. From result of analysis pearson test showed that there was a significant correlation between retinol level and hemoglobin level in pregnant women with p=0,001 (p<0,05) dan r=0,473 and there was no significant correlation between retinol level and ferritin level in pregnant women p=0,158 (p>0,05) (r=0,216). The conclusion of this study is that there is a correlation of retinol level with hemoglobin level and no correlation of retinol with ferritin level.